Financial Innovation in the Time of Pandemic: Economic Response and Global Financial Challenges - Pertiwi, Handayani Mega (Journal of Economic Growth and Development Review, 2024)
The COVID-19 pandemic has triggered an unprecedented transformation in the global financial landscape, driving rapid innovation in response to emerging economic challenges. This research analyzes the impact of the pandemic on financial innovation, investigating changes in consumer behavior, technology adoption and regulatory responses. Using a mixed methods approach, the study integrates quantitative data analysis from global surveys and industry statistics with qualitative insights from interviews with experts. Results show a significant acceleration in the adoption of digital financial services, with a 72% increase in mobile banking use and a 58% increase in contactless payments. The research also reveals increasing interest in Central Bank Digital Currencies (CBDCs) among global central banks, with 86% actively researching their potential. Although these innovations increase financial inclusion, especially in developing countries, challenges such as cybersecurity and the digital divide remain. This study highlights the need for an adaptive regulatory framework to balance innovation with financial system stability. In conclusion, the pandemic has been a catalyst for digital transformation in the financial sector, with long-term implications for monetary policy, financial inclusion and the global financial architecture. This research provides valuable insights for policymakers, financial institutions and researchers in navigating the post-pandemic financial landscape and leveraging innovation for greater economic resilience.